Letter to Jane Tolmach from Leo T. McCarthy - Leo T. McCarthy:::::: (1976)
In a May 3, 1976 personal and confidential note, Assembly Speaker Leo T. McCarthy wrote to Jane Tolmach informing her that he was enclosing "a piece of good news." He advised her to contact Bruce Lee and his organization directly. The brief message suggests supportive campaign developments and reflects McCarthy's direct communication and encouragement.